2023
DOI: 10.1039/d2ra08054k
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin: a green supramolecular catalyst assisted eco-friendly one-pot three-component synthesis of biologically active substituted pyrrolidine-2-one

Abstract: An eco-efficient protocol towards the synthesis of highly substituted bio-active pyrrolidine-2-one derivatives was demonstrated using β-cyclodextrin, a water-soluble supramolecular catalyst at room temperature under water–ethanol solvent medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The investigation revealed that when the reactions were performed using propylene carbonate (PC) as a solvent and trimethylamine as a promoter, the highest yields were achieved. Paul and co-workers [39] developed a sustainable and eco-friendly method for the synthesis of pyrrolidine-2-one (24) using a water-soluble supramolecular β-cyclodextrin as a catalyst. The 3CR of aldehydes (a) with amines (b) and dimethylacetylenedicarboxylate (DMAD) (c) was done at room temperature using water-ethanol medium to afford the products, as shown in Scheme 23.…”
Section: Green Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation revealed that when the reactions were performed using propylene carbonate (PC) as a solvent and trimethylamine as a promoter, the highest yields were achieved. Paul and co-workers [39] developed a sustainable and eco-friendly method for the synthesis of pyrrolidine-2-one (24) using a water-soluble supramolecular β-cyclodextrin as a catalyst. The 3CR of aldehydes (a) with amines (b) and dimethylacetylenedicarboxylate (DMAD) (c) was done at room temperature using water-ethanol medium to afford the products, as shown in Scheme 23.…”
Section: Green Chemistrymentioning
confidence: 99%
“…Potowski and co-workers achieved substituted α-aryl glycines (39) in a 3CR of amines (a), boronic acids (b), and glyoxalic acid (c) at room temperature using DMF as a solvent,as shown in Scheme 34 [53]. As a result, the Petasis 3CR procedure is very appealing for the manufacture of DNA-encoded small molecule screening libraries.…”
Section: Solid-phase Synthesismentioning
confidence: 99%
“…In this Please do not adjust margins Please do not adjust margins context, performing the reactions for the synthesis of pharmaceutical precursors or final active pharmaceutical ingredients (APIs) in EtOH, as a green solvent, is one of the best strategies. 10,42,52,53 Newly, tetraketone and tetrahydrobenzo[b]pyran derivatives have attracted much attention due to their biological and medicinal properties. Tetraketones are a group of chemical compounds that exist in two forms (enol-ketone tautomerism) and have antiviral, 54 antibacterial, antioxidant 55 and inhibitory properties of some enzymes such as lipoxygenase 56 and tyrosinase (reduce overproducing skin melanoma).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, performing the reactions for the synthesis of pharmaceutical intermediates or final active pharmaceutical ingredients (APIs) in EtOH, as a green solvent, is one of the best strategies. 9,41,52,53…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation